Political uncertainty and household stock market participation - Vikas Agarwal; Hadiye Aslan; Lixin Huang; Honglin Ren (University of Cologne, Centre for Financial Research (CFR), 2021)
Using micro-level panel data and a difference-in-differences identification strategy, we study the effect of political uncertainty on household stock market participation. We find that households significantly reduce their participation and reallocate funds to safer assets during periods of increased political uncertainty. The decline in participation is related to households' response to elevated asset risk and their incentive to hedge increased labor income risk. In situations where uncertainty remains high after elections, pre-election reduction in participation is only partially reversed, reflecting a prolonged distortion in household stock investments, which can have implications for households, firms, and the economy in general.
Keywords: 330; Political uncertainty; Stock market participation; Portfolio choice; Labor income risk; Asset risk